Future Playgrounds. How to Digitally Expand the City: Augmented Reality (AR) Art-pieces in Public Space - Messini, Valerie (UXUC - User Experience and Urban Creativity, 2022)
Distractions and disruptions of attention, induced by mass and social media, have become an omnipresent part of our everyday lives. Constantly online and with a device at hand, remote and digital technologies seem to shape people's behaviour more than surrounding architecture does. Even our urban tissue has become a tagged metaverse driven by chronic hyper-efficiency, simultaneity and equanimity—an accumulation of lonely humans staring into their phones. Do we still have the possibility of a collective virtual and material urban space, a shared experience, settled in built and unbuilt space alike, both beneficially interwoven into each other? In this article I will present selected works from my artistic and academic practice using Augmented Reality (AR) as a medium in an urban context. On this basis I want to discuss how our cities expand into the virtual realm through digital media and, on the other hand, I would like to demonstrate how urban space could be enhanced through playful virtuality. Conventional digital interactivity, historically rooted in video-games, is driven by protocols and efficiency. Conversely, it seems that the absence of a protocol is what conceptually differentiates playing from gaming: playing implies invention and learning, while gaming is about performing preconceived rules. Playfulness is, therefore, understood as a form of interaction capable of constituting and shaping identity and thus proves a valid method to liberate chronic hyper-efficiency-driven urban fabrics.